Od avre umetniškega dela do (psevdo)avre avtorja - Blatnik, Andrej (Primerjalna književnost, 2009)
Although post structuralism declared the death of the author, it seems that reality shows a completely different picture. In a time when products of the culture industry have lost aura, this disappearance is compensated for by the auratization of the artistic act or of the artist himself. The fascination with the sacred aura of traditional art has been replaced by the more profane glamour of artistic presentation.
Keywords: književnost; literature; mediji; communication medium; kulturna industrija; množična kultura; popularna kultura; avtor; avtorstvo